In Vitro Evaluation of Bioactivity of Chemically Deposited Hydroxyapatite on Polyether Ether Ketone - Almasi, D.; Izman, S.; Sadeghi, M.; Iqbal, N.; Roozbahani, F.; Krishnamurithy, G.; Kamarul, T.; Abdul Kadir, M. R. (International Journal of Biomaterials, 2015)
Polyether ether ketone (PEEK) is considered the best alternative material for titanium for spinal fusion cage implants due to its low elasticity modulus and radiolucent property. The main problem of PEEK is its bioinert properties. Coating with hydroxyapatite (HA) showed very good improvement in bioactivity of the PEEK implants. However the existing methods for deposition of HA have some disadvantages and damage the PEEK substrate. In our previous study a new method for deposition of HA on PEEK was presented. In this study cell proliferation of mesenchymal stem cell and apatite formation in simulated body fluid (SBF) tests were conducted to probe the effect of this new method in improvement of the bioactivity of PEEK. The mesenchymal stem cell proliferation result showed better cells proliferation on the treated layer in comparison with untreated PEEK. The apatite formation results showed the growth of the HA on the treated PEEK but there was not any sight of the growth of HA on the untreated PEEK even after 2 weeks. The results showed the new method of the HA deposition improved the bioactivity of the treated PEEK in comparison with the bare PEEK.